2019
DOI: 10.1007/s10880-019-09649-9
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Outcomes of a Cognitive Behavioral Therapy for Youth with Inflammatory Bowel Disease: Results of the HAPPY-IBD Randomized Controlled Trial at 6- and 12-Month Follow-Up

Abstract: Youth with inflammatory bowel disease (IBD) often experience psychological difficulties, such as anxiety and depression. This randomized controlled study tested whether a 3-month disease-specific cognitive behavioral therapy (CBT) in addition to standard medical care versus standard medical care only was effective in improving these youth's psychological outcomes. As this study was aimed at prevention, we included 70 youth (10-25 years) with IBD and symptoms of subclinical anxiety and/ or depression, and measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 65 publications
0
23
0
Order By: Relevance
“…It is also important to note that new studies have been published since this systematic review was completed. For example, a randomized controlled trial of young adults and adolescents (n = 70) found no evidence that disease-specific CBT along with standard medical care improved psychological symptoms or health-related QoL [102,103]. The authors concluded that this could be due to most patients having no or only mild IBD symptoms at baseline and noted that it is still unclear which patients will benefit most from CBT and how the intervention should be delivered.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to note that new studies have been published since this systematic review was completed. For example, a randomized controlled trial of young adults and adolescents (n = 70) found no evidence that disease-specific CBT along with standard medical care improved psychological symptoms or health-related QoL [102,103]. The authors concluded that this could be due to most patients having no or only mild IBD symptoms at baseline and noted that it is still unclear which patients will benefit most from CBT and how the intervention should be delivered.…”
Section: Discussionmentioning
confidence: 99%
“…The 11 included studies were randomized controlled trials investigating the physiological or psychological effects of CBT on IBD patients from 2007 to 2019. Four of these studies are from the United States [ 41 44 ], one from Australia with two follow-up times [ 45 , 46 ], two from the Netherlands [ 47 , 48 ], one from Ireland [ 49 ], one from England [ 50 ] and one from New Zealand [ 51 ]. The sample size of the studies ranged from 41 to 199, making a total of 995 individuals two studies used the same cohort).…”
Section: Resultsmentioning
confidence: 99%
“…Only two studies included only 41 participants [ 41 , 44 ]. All the included studies reported follow-up data for at least 3 months, with six of them followed for 12 months or more [ 41 , 43 , 45 47 , 50 ], and the longest took 2 years [ 45 ]. Details can be found in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations